(3eLehY eNJUQ GHf GdYOjes - (3ceGd GdOjf YeQ Hf YHO GdYRjR GdeYQha HGHf GdYOje GdMdis ((3eMeO Hf CHj HcQ Hf CMeO Hf YeQ s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdeJaVd Ydi YHGOg HHdhZ GdBeGd hGdefYe Ydi ef jTGA MQa GdCda s
(3BNQgG (B:s
(3hGdYJb HTQi HGdZfG jG PG GdZfG aCeff Ydi GdaGfi jYJb GdHGbi s
(3GdfSNI HgG MhGTs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdHdOjI HGdCScfOQjI (B(3611(3L(B) s
Keywords: (3GdMOjK h GdeUWdMs